Perilaku sedentari sebagai faktor risiko kejadian obesitas pada anak sekolah dasar di Kota Yogyakarta dan Kabupaten Bantul - Andi Imam Arundhana; Hamam Hadi; Madarina Julia (Alma Ata University Press, 2013)
ABSTRACTBackground: According to Basic Health Research (Riskesdas) 2010 the prevalence of obesity in Yogyakarta was 78% in 2010. Increasing prevalence of obesity in school children is mainly related to sedentary activities and decreasing medium-high physical activities.Objective: To ﬁ nd out whether sedentary behavior was risk factor for obesity in school children and identify the level of its contribution.Method: The study used case-control design. Population consisted of elementary school (either state or private) children of grade 1-5 at Yogyakarta and Bantul. The selection of school during screening phase was based on probability proportional to size (PPS) method. The choice of cases in children diagnosed obese during screening phase used simple random sampling supported with random table tool and matching of school. Based on sample basic calculation there were 488 samples consisting of 244 cases and 244 controls. Data of physical activities were obtained through modiﬁ ed questionnaire on children’s physical activities (CPAQ). Data were processed using software of Epidata v 3.1 and STATA v.11. Analysis used univariate, bivariate, and multivariate analysis with t-test, anova, and logistic regression. Result: Duration of sedentary behavior in obese students was longer than those not obese with average difference 49.81 minutes/day (p<0.01). The result of Chi-square analysis showed sedentary activities had signiﬁ cant correlation with the incidence of obesity with OR=6.93 (95%CI: 4.56-10.54). Based on types of sedentary activities, there was signiﬁ cant correlation for category of screen based and sitting around (p<0.05).Conclusion: Sedentary behavior was risk factor for the incidence of obesity in elementary school children. Average duration of sedentary activities of obese children was higher than those not obese. Based on residency, average duration of sedentary activities of obese children in urban area was higher than those living in rural area. KEYWORDS: physical activities, overweight, rural, urban, elementary school childrenABSTRAKLatar belakang: Berdasarkan Riset Kesehatan Dasar (Riskesdas) tahun 2010, prevalensi obesitas di Yogyakarta adalah 78% pada tahun 2010. Peningkatan prevalensi obesitas pada anak sekolah sangat berkaitan dengan aktivitas sedentari dan berkurangnya aktivitas ﬁ sik.Tujuan: Untuk Mengetahui apakah perilaku sedentari merupakan faktor risiko terhadap obesitas anak sekolah dan mengidentiﬁ kasi seberapa besar kontribusinya.Metode: Penelitian ini merupakan penelitian kasus kontrol. Populasi terdiri dari anak-anak sekolah dasar (baik negeri maupun swasta) kelas 1-5 di Yogyakarta dan Bantul. Pemilihan sekolah selama fase skrining berdasarkan metode probability proportional to size (PPS). Kasus adalah anak-anak yang didiagnosis obesitas pada saat fase skrining, menggunakan simple random sampling didukung dengan tabel random dan dilakukan matching pada sekolah tersebut. Berdasarkan perhitungan sampel, terdapat 488 sampel yang terdiri dari 244 kasus dan 244 kontrol. Data aktivitas ﬁsik diperoleh menggunakan formulir CPAQ. Data diproses menggunakan Epidata v 3.1 and STATA v.11. Analisa data yang digunakan adalah univariat, bivariat, and analisa multivariat dengan t-test, anova, dan logistic regression.Hasil: Durasi perilaku sedentari pada siswa obesitas lebih lama dibandingkan mereka yang tidak obesitas dengan ratarata perbedaan 49,81 menit/hari (p<0,01). Hasil analisis Chi-square menunjukkan perilaku sedentari memiliki hubungan yang signiﬁkan dengan kejadian obesitas dengan OR=6.93 (95%CI: 4,56-10,54). Berdasarkan jenis perilaku sedentari, terdapat hubungan yang signiﬁkan untuk kategori screen based dan duduk-duduk (p <0,05).Kesimpulan:Perilaku sedentari merupakan faktor risiko terhadap kejadian obesitas pada anak-anak sekolah dasar. Rata-rata durasi perilaku sedentari pada anak yang obes lebih tinggi dibandingkan anak yang tidak obes. Berdasarkan tempat tinggal, rata-rata durasi perilaku sedentari pada anak obes di kota lebih tinggi dibandingkan yang di desa.KATA KUNCI: aktivitas ﬁ sik, overweight, desa, kota, anak SD